Utilizarea arduino pentru elaborarea aplicaţiei mobile de monitorizare a temperaturii [Articol] - Andronic, Roman (CEP USM, 2022)
This work presents the development of an application that monitors the temperature in real time and can be accessed remotely through the internet. The user obtains without much expense an application that is easy to use both for domestic purposes and in professional fields. In order to achieve this goal, an easy application for monitoring has been developed, using a NodeMCU board with integrated WIFI module ESP8266.
Keywords: aplicația mobilă